Improving the learning experience of business students - Tan, Mei Nah. (2008)
This practicum examines how the Diploma in Business Information Technology sought to improve the teaching and learning experience of its students in the study of E-Business Management, using a different strategy through Problem-Based Learning (PBL) by providing students with authentic, real-lift problems to solve, with an emphasis of the use of Information Technology (IT) in applying the knowledge learned through creation of a virtual storefront using a software.